2021
DOI: 10.1002/ceat.202100239
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrodeoxygenation of Model Bio‐oils Using HZSM‐5 and Ni2P/HZM‐5 Catalysts: Comprehension of Interaction

Abstract: Hydrodeoxygenation (HDO) of Mixture 1 (acetic acid and phenol) and Mixture 2 (acetone, acetic acid, phenol, 4-ethylguaiacolis, furfural, and water) as model biooils was performed to investigate the interactions. Ni 2 P/HZSM-5 catalysts exhibited higher activity than blank HZSM-5. The conversion rate of acetic acid enhanced with the increase of temperature, contrary to the value of phenol due to the differential adsorption capacity on active phases. Acetone can be formed by self-ketonization of acetic acid. Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Fuels 2023, 4 187 However, the application of phenol obtained from pyrolysis oil is limited due to fewer reactive sites and steric hindrance. For this reason, it is very necessary to upgrade biooil [19,[21][22][23][24][25]. In our previous study [26], the combination of the two environmentally friendly methods (fractional condensation and water extraction) was successful in separating phenolic compounds from beechwood pyrolytic oil.…”
Section: Introductionmentioning
confidence: 99%
“…Fuels 2023, 4 187 However, the application of phenol obtained from pyrolysis oil is limited due to fewer reactive sites and steric hindrance. For this reason, it is very necessary to upgrade biooil [19,[21][22][23][24][25]. In our previous study [26], the combination of the two environmentally friendly methods (fractional condensation and water extraction) was successful in separating phenolic compounds from beechwood pyrolytic oil.…”
Section: Introductionmentioning
confidence: 99%
“…Literature sources report that BPT contains a high amount of oxygenated compounds such as ketones, phenols, furans, organic acids, ethers, and aldehydes [8]. Most of the previous studies focused on a single model compound for BPT-DO process analysis, such as furfural [9], 2-methylfuran [10], phenol [11], quaiacol [12], acetic acid [13], 2-furyl methyl ketone [14], and acetone [15]. Some researchers explained the interaction between oxygenated BPT compounds and proposed reaction routes using a mixture of model compounds due to the complexity of BPT.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that HZSM-5 activity increased when Ni 2 P was loaded into the surface of the blank zeolite, thus increasing the conversion of acetic acid and decreasing the conversion of phenol with the increasing temperature due to the adsorption competition on the active sites. Moreover, higher temperatures led to increased production of aromatics and substituted phenols through the alkyl substitution of benzene and phenol, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, the direct use of bio-oil as a source of phenol is limited due to the relatively low concentration of reactive sites; thus, an upgrading step is necessary. 17,[20][21][22][23][24] In our previous study, 19 the combination of fractional condensation and water extraction methods was used to successfully separate phenolic compounds from the beech wood pyrolytic bio-oil. After a fractional condensation, the extraction of bio-oil by water was able to extract phenol into the water-insoluble fraction.…”
Section: Introductionmentioning
confidence: 99%